(untitled) (Altre Modernità, 2024)
From Lu Xun’s choice to heal Chinese people with a literary movement instead than medicine in 1922 to “scar literature” (shanghen wenxue 伤痕文学), which first re-elaborated Maoist past in the late 1970s, the metaphor of the “cure” has been widely used to describe the function of literature within Chinese society since modern times. It seems therefore justified to read the representation of medicine in fictional works, especially those dealing with historical trauma, as an allegory. In the paper, I examine in these terms the recounting of the famine that stroke the Chinese countryside after the Great Leap Forward (1958-62), a period chosen both for its contested inclusion in collective memory and for the representation of illness it imposes. From an overview of some of the few novels set in those years (by authors such as Zhang Yigong, Liu Qingbang, Zhi Liang, Yan Lianke, Mo Yan), a recurrent negative connotation of the doctors emerges: when not directly harmful, they are either absent, passive, or impeded in acting. I suggest that this pessimistic depiction symbolizes not only the historically attested neglect of, and refusal to “heal”, rural areas during the crisis, but also literature’s struggle to play a therapeutic role in a context of denied collective trauma.